Improving Science-Society dialogue requires practice : Commentary - Horst, Maja; Carsten Nielsen, Sofie (STS Encounters, 2015)
In order to focus attention on the science-society relationship the Ministry for Higher Education and Science organized a conference on Responsible Research and Innovation in December 2014 in collaboration with Maja Horst. This comment explains the background and the outcome of this conference. The comment is not intended as an academic analysis but rather as a normative statement on the ways forward towards a robust knowledge society and a fruitful implementation of the idea of responsible research and innovation.